Design of Carborane Molecular Architectures via Electronic Structure Computations - Josep M. Oliva; Luis Serrano-Andrés; Douglas J. Klein; Paul von Ragué Schleyer; Josef Michl (International Journal of Photoenergy)
Quantum-mechanical electronic structure computations were employed to explore initial steps towards a comprehensive design of polycarborane architectures through assembly of molecular units. Aspects considered were (i) the striking modification of geometrical parameters through substitution, (ii) endohedral carboranes and proposed ejection mechanisms for energy/ion/atom/energy storage/transport, (iii) the excited state character in single and dimeric molecular units, and (iv) higher architectural constructs. A goal of this work is to find optimal architectures where atom/ion/energy/spin transport within carborane superclusters is feasible in order to modernize and improve future photoenergy processes.